Employee allocation in Slovak companies - Stachová, Katarína; Stacho, Zdenko (Business: Theory and Practice, 2013)
Employee allocation is a part of the process of workforce formation (staffing) in organisation. Its aim within hiring new employees and internal mobility is to have an adequate, stable and satisfied employee in the shortest possible time, and its key objective within employment termination is to ensure a fair departure. Employee allocation results in optimal usage of financial means of organisation as well as in development of abilities of employees and teams in accordance with the aims of organisation. The aim of our research conducted in 2012 was to find out whether organisations operating in Slovakia realize the importance of employee allocation. Research results imply that only 14 % of organisations deal with adaptation comprehensively, i.e. at all three levels. And only 8 % of interviewed organisations deal with outplacement.